The relationship between teacher commitment, teacher self-efficacy, and work-related quality of life among science teachers - Omar T. Bataineh; Ahmad M. Mahasneh; Zohair H. Al-Zoubi; Ahmad Qablan; Ahmed M. Alkaabi (PLoS ONE, 2025)
This study examines the validity and reliability of the Arabic versions of the Teacher Commitment Scale, Teacher Self-Efficacy Scale, and Work-Related Quality of Life Scale. It explores the relationships among these variables in Jordan. A total of 616 science teachers participated by completing the three scales. Exploratory factor analysis indicated that the Arabic version of the Teacher Commitment Scale comprised four factors explaining 62.49% of the variance; the Teacher Self-Efficacy Scale consisted of one factor accounting for 60.22% of the variance; and the Work-Related Quality of Life Scale included six factors explaining 74.14% of the variance. Results showed statistically significant relationships among teacher commitment, self-efficacy, and quality of life. Future research should explore additional variables influencing teacher commitment.